KESAN PENILAIAN KINERJA, STRUKTUR ORGANISASI DAN KINERJA KERJA GURU - Akhir Lusono; Wahyu Eko Prasetyanto (Lembaga Pengembangan Kinerja Dosen, 2022)
This study examines the impression of performance appraisal and organizational structure as a correlation of school teacher performance in the Special Region of Yogyakarta. The population of this study consisted of 13,039 public secondary school teachers in the Province of the Special Region of Yogyakarta. By using simple random sampling technique, as many as 440 respondents. Three (3) questionnaires developed by the researcher; entitled: Organizational Structure Questionnaire (OSQ), Performance Assessment Impression Questionnaire (PAIQ), and Teacher Performance Questionnaire (TJPQ) with reliability coefficients of 0.73, 0.69 and 0.76 were used for data collection. It was found that there was a significant relationship between organizational structure and teacher performance in public secondary schools in the Special Region of Yogyakarta in the order (r = 0.191, P<.05). It was also found that there was a significant relationship between performance appraisal impressions and the performance of public secondary school teachers in the Special Region of Yogyakarta in the order (r = 0.112, P<.05). There is a significant joint contribution of the independent variables (organizational structure and impression of performance appraisal) to the dependent variable (performance of public secondary school teachers); R = 0.457, P < 0.05. It was further revealed that 32.0% (Adj. R2 = 0.320) that about 33% of the variance in the performance of public secondary school teachers was due to a linear combination of organizational structure and performance appraisal impressions. Organizational structure and performance appraisal impressions were found to be significant and highly determine the performance of school teachers with a P value of less than 0.05 and the magnitude of the organizational structure (ÿ = 0.265, t = 5.328, P<.05) and performance appraisal impressions (ÿ = 0.193, t). = 3.644, P<.05).